Applying consumer-based brand equity in luxury hotel branding - Liu, M.; Wong, I.; Tseng, T.; Chang, A.; Phau, Ian (Elsevier, 2016)
This study examines the effects of consumer-based brand equity (CBBE) components (i.e., brand loyalty, brand awareness, perceived quality, and brand image) of luxury hotel brands on consumer brand attitude and purchase intention with brand performance as a contextual factor. Through a survey involving 327 tourists conducted in luxury hotels in Macau, results reveal that all four CBBE elements positively relate to brand attitude, and three directly influence purchase intention. Brand attitude mediates the relationship between four CBBE elements and purchase intention, and brand performance moderates the relationship between brand attitude and purchase intention. This study expands CBBE theory to include luxury hotel brands and contributes to the literature by clarifying the direct, indirect, and total effects of each CBBE element on brand attitude and purchase intention. In addition, the study identifies brand performance as a contextual factor rather than a consequence of brand equity and brand attitude.